Massive proteinuria as prognostic factor for maternal-fetal morbimortality in patients suffering severe preeclampsia: a case report and literature review - Castillo-Zamora, Marcos; Álvarez-Jaramillo, Juliana; Escandón-Barón, Ana María; Márquez-Duque, Juan Manuel; Páramo-Díaz, Laura Isabel; Rojas-Figueroa, Ana Carolina (Revista Colombiana de Obstetricia y Ginecología, 2012)
Objective: Presenting the case of a 19-year-old twenty-four weeks pregnant female who had been diagnosed with severe preeclampsia and neophrotic-range proteinuria and reviewing the physiopathology, histopathology and prognosis of massive proteinuria in severe preeclampsia patients. Materials and methods: the case of a 19-year-old twenty-four weeks pregnant G1P0 patient having 120/90 mmHg blood pressure figures is presented; she was hospitalized in the Universidad de la Sabana teaching hospital, a high-complexity private hospital due to 220 mg/dl isolated proteinuria for classification of hypertensive disorder during pregnancy. the proteinuria study gave an initial 9 g/24 hours result. Additional exams were requested for preeclampsia; these came within normal ranges. Periodic 24 hour proteinuria studies were made, revealing a tendency to increase (14 g maximum). She then presented high blood pressure in a range of severity associated with symptoms of vasospasm and imminent eclampsia; the pregnancy was thus terminated at 25.4 weeks by caesarean (the newborn dying afterwards). the patient continued to have high blood pressure figures during the puerperium, requiring anti-hypertensive management. Adequate control was finally achieved and she was discharged. A search was made of the pertinent medical literature relating to the case in Medline/PubMed, JStOR and Lilacs databases using the MeSH search terms "pregnancy", "preeclampsia", "proteinuria", and "nephrotic syndrome". Results: 26 articles were found, 11 of them being related to proteinuria within a state of preeclampsia. A snowball search was then made from these, leading to another 38 articles. Conclusion: the presence of massive proteinuria and its association with preeclampsia has still not been clearly elucidated. Ranges of proteinuria must thus be established within criteria regarding severity which lead to further maternal-fetal complications developing.